Italiano sem fronteiras: enunciação, política e identidades na Universidade Federal de Santa Maria - Araujo, Marlon da Fonseca Misceno (2023)
The present study, entitled “Italian without Borders: Enunciation, Politics and Identities at the Federal University of Santa Maria”, aims at understanding the identity and cultural relations mobilized by the participants of the Italian courses offered by the Language without Borders (IsF), of the Andifes IsF Network, within the scope of the Federal University of Santa Maria (UFSM). The specific objectives are: to contextualize the Italian language teaching space of Idiomas sem Fronteiras at UFSM; to characterize the profile of UFSM students who enroll in Italian courses; to discuss the main motivations for the participation of students in Italian courses at Idiomas sem Fronteiras; to verify the enunciation and the identity relations that cross the studies of the Italian language. The theoretical contribution is based on the concepts of enunciation proposed by Émile Benveniste and on the “Semantics of the Event” proposed by Eduardo Guimarães. As instruments of analysis, forms were used, already created by the IsF of UFSM, on the Google Forms platform, to receive registrations and feedback on courses given by academic subjects (students, professors and employees) who assume the position of students of Italian who are interested and /or enrolled in the beginner level course “Introduction to Italian language and culture 1 - A1”, from November 2021 to May 2022. By contributing to the internationalization of the academic space, for the UFSM academic community, the Languages without Borders provides a first formal approach to the standard Italian language. Starting from the idea of multiplicity that is present in the Italian context due to the existence of different languages and that is also shared with the history of Rio Grande do Sul, through the Italian heritage and the establishment of the Fourth Colony near Santa Maria, this work seeks to identify the effects of meaning in relation to the study of the Italian language in the university space of UFSM. Students seek to relate their first languages with the Italian language practiced at the IsF using utterances that end up being political acts, as they establish a closer relationship between different cultures and assume new meanings in enunciation, made possible by the enunciative scene established within the university. It is hoped that the study will contribute to future research in university language policy and in aspects that refer to the meanings of identification and cultural relations in the panorama of the plurality of Brazilian languages.